AZURE AI MARKET ANALYSIS AND FORECASTING: TRANSFORMING BUSINESS INTELLIGENCE - Narasimha Rao Oruganti, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This thorough article looks at Azure AI's forecasting and market analysis capabilities as well as how these capabilities are revolutionizing corporate intelligence. It looks at how businesses use AI technologies to obtain a competitive edge in the quickly changing business environment of today. The article explores the platform's fundamental features, such as sophisticated data processing, machine learning applications, and real-time analytics, while emphasizing its noteworthy contributions to predictive modeling and strategic decision support. It also discusses recommended practices, success metrics, and implementation issues that businesses should think about when implementing Azure AI solutions. This article illustrates how Azure AI's advanced analytics platform helps businesses to transform raw data into actionable insights, eventually boosting operational efficiency and competitiveness in the market, by carefully examining industry trends and enterprise adoption patterns.